2022
DOI: 10.1136/jitc-2021-004133
|View full text |Cite
|
Sign up to set email alerts
|

BCG hydrogel promotes CTSS-mediated antigen processing and presentation, thereby suppressing metastasis and prolonging survival in melanoma

Abstract: BackgroundThe use of intralesional Mycobacterium bovis BCG (intralesional live BCG) for the treatment of metastatic melanoma resulted in regression of directly injected, and occasionally of distal lesions. However, intralesional-BCG is less effective in patients with visceral metastases and did not significantly improve overall survival.MethodsWe generated a novel BCG lysate and developed it into a thermosensitive PLGA-PEG-PLGA hydrogel (BCG hydrogel), which was injected adjacent to the tumor to assess its ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Although earlier studies had confirmed that IRF1 regulates the endogenous expression of cathepsin S(CTSS), 22,23 there is no proof that the IRF1‐mediated CTSS pathway regulates antigen presentation. Nevertheless, DC maturation and antigen processing and presentation are ascribed to the regulation of CTSS in earlier studies 43 . Our data showed that downregulated IRF1 resulted in the decreased expression of CTSS in cDC2 and eventually suppressed the activation of CD4 + T cells.…”
Section: Discussionmentioning
confidence: 48%
“…Although earlier studies had confirmed that IRF1 regulates the endogenous expression of cathepsin S(CTSS), 22,23 there is no proof that the IRF1‐mediated CTSS pathway regulates antigen presentation. Nevertheless, DC maturation and antigen processing and presentation are ascribed to the regulation of CTSS in earlier studies 43 . Our data showed that downregulated IRF1 resulted in the decreased expression of CTSS in cDC2 and eventually suppressed the activation of CD4 + T cells.…”
Section: Discussionmentioning
confidence: 48%
“…Heatmaps, correlation plots, and principal component analysis plots were created in R Studio (Rstudio Inc., Boston, USA). Gene expression data were generated with Nanostring arrays or retrieved from the indicated, pre-existing, open-access RNA sequencing data sets ( 31 , 32 ).…”
Section: Methodsmentioning
confidence: 99%
“…BCG can be injected directly into the lungs to stimulate an immune response against cancer cells. It can be administered alone or in conjunction with other therapies, such as chemotherapy or radiation therapy ( 355 ).…”
Section: New Strategies For Prevention and Combating Immunotherapy Re...mentioning
confidence: 99%